MODEL PENDIDIKAN BEHAVIORISTIK DALAM ISLAM - Sutarto Sutarto (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2023)
The behavioristic education model in Islam is a learning approach that focuses on changing individual behavior through the use of positive reinforcement and sanctions. In Islam, this model can be applied by integrating Islamic values in the learning approach, so that it can help individuals to achieve predetermined educational goals. In its application, this model requires consistency, attention to individual conditions, as well as continuous evaluation and improvement in order to provide maximum benefits for individuals and society. In the behavioristic education model, educators focus their attention on visible behavior, to form the desired behavior. This model is applied by giving rewards or rewards for good behavior and strengthening this behavior. Conversely, sanctions or punishments are given for bad behavior, so that individuals can learn to avoid unwanted behavior. In conclusion, the behavioristic educational model in Islam can be an alternative in the development of learning approaches that can help individuals to achieve predetermined educational goals. In its application, this model requires special attention to Islamic values as well as consistency and continuous evaluation. Thus, the development of a behavioristic educational model in Islam can provide good benefits for individuals and society. Suggestions and recommendations have been put forward, such as the integration of Islamic values, attention to individual conditions, consistency in application, training and education for educators, as well as continuous evaluation and improvement.